Ответ:
1) (3x²sinx-x³cosx)/sin²x
Объяснение: [tex]y=\frac{x^3}{sinx}[/tex]
[tex]y'=(\frac{x^3}{sinx})'=\frac{(x^3)'sinx-x^3(sinx)'}{sin^2x}=\boxed{\frac{3x^2sinx-x^3cosx}{sin^2x} }[/tex]
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
1) (3x²sinx-x³cosx)/sin²x
Объяснение: [tex]y=\frac{x^3}{sinx}[/tex]
Формулы:
Таблица производных:
Находим производную нашей ф-ции:
[tex]y'=(\frac{x^3}{sinx})'=\frac{(x^3)'sinx-x^3(sinx)'}{sin^2x}=\boxed{\frac{3x^2sinx-x^3cosx}{sin^2x} }[/tex]